La recepción de Hildegarde de Bingen en los siglos XIII y XIV - Santos Paz, José Carlos (1998)
"Hildegard of Bingen (1098-1179) won a double reputation in the last centuries of the Middle Ages. Through her writings, she became famous as a visionary and authoress of scientific texts, whilst she was considered a prophetess due to a series of apocryphal prophecies. In this thesis we intend to study such reputation as prophetess and to prove how this determined her fame during the 13th to the 15th centuries. Her prophecies in future times and the Antichrist can be found in the Speculum futurorum temporum sive Pentacronon sancte Hildegardis, a compilation made by the Cistercian Gebeno of Eberbach around the year 1220. The first part of our work contains the edition of the first redaction of the mentioned compilation, which includes more than one hundred manuscripts, and a study of its influence, giving special relevance to the Epistola de schismate by Heinrich of Langenstein (of which we also includ a critical edition). The second part is devoted to two pseudohildegardian prophecies: one beginning by Insurgent gentes written around 1250, in the context of the Parisian controversy, against the Franciscans and the Dominicans; the other one, beginning by Vidi ab aquilone, is a series of predictions. Both prophecies (of which we can find several versions) are edited here. We also include the edition of an unpublished commentary to the first one (Insurgent gentes), made by the Aragonese Dominican Gerónimo Bautista of Lanuza. The manuscripts I have knowledge of with by Hildegard of Bingen, Gebeno and pseudolhildegardian prophecies, are all gathered here with a brief description of each."